Sweetening pharmaceutical radiochemistry by (18)f-fluoroglycosylation: a short review - Maschauer, Simone; Prante, Olaf (BioMed Research International, 2014)
At the time when the highly efficient [(18)F]FDG synthesis was discovered by the use of the effective precursor 1,3,4,6-tetra-O-acetyl-2-O-trifluoromethanesulfonyl- ? -D-mannopyranose (mannose triflate) for nucleophilic (18)F-substitution, the field of PET in nuclear medicine experienced a long-term boom. Thirty years later, various strategies for chemoselective (18)F-labeling of biomolecules have been developed, trying to keep up with the emerging field of radiopharmaceutical sciences. Among the new radiochemical strategies, chemoselective (18)F-fluoroglycosylation methods aim at the sweetening of pharmaceutical radiochemistry by providing a powerful and highly valuable tool for the design of (18)F-glycoconjugates with suitable in vivo properties for PET imaging studies. This paper provides a short review (reflecting the literature not older than 8 years) on the different (18)F-fluoroglycosylation reactions that have been applied to the development of various (18)F-glycoconjugate tracers, including not only peptides, but also nonpeptidic tracers and high-molecular-weight proteins.
EVALuna2:13826